Identifikasi Asam Lemak Penyusun Minyak Biji Karet (Hevea Brasiliensis) Menggunakan GC-MS - Ismiyarto, Ismiyarto; Prasetya, Nor Basid Adiwibawa; Wibawa, Pratama Jujur (Jurnal Kimia Sains dan Aplikasi, 2003)
Isolation of rubber seed (Hevea brasiliensis) oil have carried out by using soxhlet extraction with n-hexane as solvent. This research have been determined of fatty acid composition of rubber seed oil. Separation of free fatty acid from triglyceride done by ethanol 96 %. The oil phase was analysed by gas chromatography - mass spectrophotometer. It was resulted five chromatogram peaks of fatty acid methyl ester, there are methylester from palmitic acid (9.12%), linoleic acid (44.69 %), elaidic acid (44.69 %), stearic acid (8.89 %>) and 11,14-eicosadienoic acid (5.30 %) respectively.